How to avoid mistakes in diagnostics of epilepsy - Jędrzejczak, Joanna (Przewodnik Lekarza/Guide for GPs, 2005)
There are many mistakes to be made in diagnostics of epilepsy that implies inefficient pharmacological therapy. Such mistake is frequently cause of drug-resistant epilepsy. Anamnesis and witness observations are very important in correlation with additional examinations. Generalized and localized epilepsies are divided according to causes also into secondary and idiopathic with different epidemiology, symptoms and patomechanisms. Other types of epilepsy are also to be considered.